2017
DOI: 10.1007/s11894-017-0589-2
|View full text |Cite
|
Sign up to set email alerts
|

Ablation Therapy for Barrett’s Esophagus: New Rules for Changing Times

Abstract: Patients with T1a esophageal adenocarcinoma and BE of high-grade dysplasia should undergo endoscopic ablative therapy. The most studied technique to date is radiofrequency ablation. It can be combined with endoscopic mucosal resection in cases containing nodular and flat lesions. Cryotherapy and APC have shown promise with good efficacy and safety profiles so far, but are not mainstream as more studies are needed. Surveillance is still required post-ablation since recurrence is common. Low-grade dysplasia can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The APE study evaluated the efficacy of APC versus surveillance for patients who had undergone EMR for neoplastic BE. The study showed a decrease in residual (secondary) lesions with APC (3% versus 36%) and the need for secondary therapy . The hybrid APC technique (submucosal injection of saline prior to thermal ablation) also showed promising results in a study by Manner et al .…”
Section: Treatmentmentioning
confidence: 95%
See 3 more Smart Citations
“…The APE study evaluated the efficacy of APC versus surveillance for patients who had undergone EMR for neoplastic BE. The study showed a decrease in residual (secondary) lesions with APC (3% versus 36%) and the need for secondary therapy . The hybrid APC technique (submucosal injection of saline prior to thermal ablation) also showed promising results in a study by Manner et al .…”
Section: Treatmentmentioning
confidence: 95%
“…EMR is the treatment of choice for nodular disease, short segment disease, and focal lesions in long‐segment BE. Multiple studies have demonstrated that complete eradication of intestinal metaplasia (CE‐IM) is high (80–85%) . However, the long‐term recurrence rate varies from 16% to 39% for CE‐IM and 6% for recurrence after achieving complete eradication of neoplasia (CE‐N) respectively.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 There is insufficient evidence to support eradication of IM in the absence of dysplasia. 47 Complete eradication of IM can be achieved in various ways. In Western nations the mucosal lesion or dysplastic area is usually found within a significantly long segment of BE rather than in a short segment that is amenable to a onestep approach of therapy.…”
Section: Ablation Of Dysplasia and Intestinal Metaplasiamentioning
confidence: 99%